2022
DOI: 10.1097/sla.0000000000005369
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Ineffective Esophageal Motility on Patients Undergoing Magnetic Sphincter Augmentation

Abstract: Objective: To evaluate and characterize outcomes of MSA in patients with IEM. Summary Background Data: MSA improves patients with gastroesophageal reflux and normal motility. However, many patients have IEM, which could impact the outcomes of MSA and discourage use. Methods: An international, multi-institutional case control study of IEM patients undergoing MSA matched to normal patients was performed. Primary outcomes were new onset dysphagia and need for postoperative interventions.Results: A total of 105 IE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Early tenets of ARS suggested that a diagnosis of IEM should prompt a tailored fundoplication to mitigate postoperative dysphagia. 17 However, in recent years multiple studies have shown similar rates of dysphagia after partial or complete fundoplication in patients with IEM, calling into question the utility of the definition once again. 18,19 The CCv4.0 released in November 2020 included major revisions to the definition of IEM.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Early tenets of ARS suggested that a diagnosis of IEM should prompt a tailored fundoplication to mitigate postoperative dysphagia. 17 However, in recent years multiple studies have shown similar rates of dysphagia after partial or complete fundoplication in patients with IEM, calling into question the utility of the definition once again. 18,19 The CCv4.0 released in November 2020 included major revisions to the definition of IEM.…”
Section: Discussionmentioning
confidence: 99%
“…The major concern with IEM and ARS is whether the patient's esophageal body will be able generate enough force to overcome the increased resistance at the EGJ. Early tenets of ARS suggested that a diagnosis of IEM should prompt a tailored fundoplication to mitigate postoperative dysphagia 17 . However, in recent years multiple studies have shown similar rates of dysphagia after partial or complete fundoplication in patients with IEM, calling into question the utility of the definition once again 18,19 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dominguez-Profeta et al [89] found that adequate peristaltic reserve using the DCI after multiple rapid swallows correlated with a decreased incidence of dysphagia following MSA implantation. In a multicenter study including 210 patients, 105 with IEM and 105 without IEM, Baison et al [90] found that age > 45 years, preoperative dysphagia, MSA size < 15 beads, and < 40% intact swallows on preoperative manometry were independent risk factors for the need of endoscopic dilation or device removal. All patients requiring removal had a DCI < 200 mm Hg and < 20% intact swallows.…”
Section: High-resolution Manometry and Impedance Planimetry Findingsmentioning
confidence: 99%